Digital Marketing Dissemination of Health Supplement Products at SNS21 Inc. - Muhammad Ibnu Aqil; Salsa Maulidya Rahmi; Septiana Budi Rahayu; Dhanar Intan Surya Saputra; Riyanto Riyanto (Peneliti Teknologi Teknik Indonesia, 2023)
Digital Marketing is one of the marketing media trends that has many enthusiasts, including the public, supporting various buying and selling activities that are carried out. Gradually, people are starting to switch from conventional marketing models to modern marketing, namely digital marketing. With Digital Marketing, communication, and transactions can be carried out at any time, covering large areas and various corners of the world. In this digital era, the number of social media users, both chat-based and application-based, is increasing day by day. This is an opportunity for entrepreneurs to expand their market by using smartphones. PT. Sukses Nusantara Sakti 21 (SNS21 Inc.) is an international-scale company engaged in the general trading of health supplement products. SNS21 Inc.'s partner problems, namely the inability to use the WhatsApp Business feature. In this case, the implementation of this activity uses the direct training method with a seminar approach. The results will provide motivation and training in using WhatsApp Business through mentors who are experienced in digital communication so that they can help promote SNS21 Inc partner products. The result of a series of activities shows that partners can build digital branding and marketing and increase sales of health supplement products.